Respuesta :
The answer is the last option (Option D), which is:
D. 25
The explanation is shown below:
1. You have that:
(a ± b)^2=a^2 ± 2ab + b^2
2. The expression given in the problem is:
x^2-10x+n
Where x^2=a and 2ab=10x
2b=10
b=10/2
b=5
3. Therefore, you have:
b^2=5
b^2=25
b^2=n
n=25
D. 25
The explanation is shown below:
1. You have that:
(a ± b)^2=a^2 ± 2ab + b^2
2. The expression given in the problem is:
x^2-10x+n
Where x^2=a and 2ab=10x
2b=10
b=10/2
b=5
3. Therefore, you have:
b^2=5
b^2=25
b^2=n
n=25
Answer:
the answer is 25!!
Step-by-step explanation:
I hope this is helpful to sum of y'all!!